2014
DOI: 10.1371/journal.pone.0095050
|View full text |Cite
|
Sign up to set email alerts
|

Larval Dispersal Modeling of Pearl Oyster Pinctada margaritifera following Realistic Environmental and Biological Forcing in Ahe Atoll Lagoon

Abstract: Studying the larval dispersal of bottom-dwelling species is necessary to understand their population dynamics and optimize their management. The black-lip pearl oyster (Pinctada margaritifera) is cultured extensively to produce black pearls, especially in French Polynesia's atoll lagoons. This aquaculture relies on spat collection, a process that can be optimized by understanding which factors influence larval dispersal. Here, we investigate the sensitivity of P. margaritifera larval dispersal kernel to both p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 45 publications
2
51
1
Order By: Relevance
“…Work by Thomas et al [107] in French Polynesia on connectivity between populations discovered that larval sink and source locations for P . margaritifera accounted for 26% and 59% of the variation observed respectively, underscoring its importance for larval supply and management of farmed and wild pearl oysters.…”
Section: Resultsmentioning
confidence: 99%
“…Work by Thomas et al [107] in French Polynesia on connectivity between populations discovered that larval sink and source locations for P . margaritifera accounted for 26% and 59% of the variation observed respectively, underscoring its importance for larval supply and management of farmed and wild pearl oysters.…”
Section: Resultsmentioning
confidence: 99%
“…Our results seem to indicate that the northeastern samples are not well connected to the rest of the lagoon: they are made of larger, older individuals, mostly females (up to 86%), all with a specific "northeastern" genetic signature, meaning they are not replenished by larval recruitment from either the exploited stock, or the southwestern natural stock. Previous research using modelling of larval dispersal showed the existence of two hydrodynamic systems in Ahe, separating the northeastern lagoon from the southwestern lagoon [7]. The model showed that wind and resource distribution patterns averaged over the years favored two dominant dispersal dynamics: (i) self-recruitment within each hydrodynamic system and (ii) east to west transfers, but very rarely west to east transfers [7,8].…”
Section: Demographic and Genetic Analysis Of The Natural Stockmentioning
confidence: 89%
“…Among the six sets of collectors deployed in the lagoon, the set #6 could not be located in May and was considered lost. From the five collectors left, we collected a total of 41 individuals (21,8,7,4 and 1 individual from C3, C5, C1, C4 and C2 respectively).…”
Section: Size and Sex Of Sampled Individualsmentioning
confidence: 99%
See 2 more Smart Citations